Numerical simulation of hydrogen adsorption and dissociation mechanisms on the surface of high-grade steel - Xia WU; Jindou LIU; Lan LAN; Zihan SONG; Wenlong JIA (You-qi chuyun)
ObjectiveThe dissociation of hydrogen into hydrogen atoms is identified as the primary factor contributing to damage resulting from hydrogen permeation and embrittlement in hydrogen-enriched compressed natural gas (HCNG) transmission pipelines. Current research primarily focuses on the α-Fe microstructure of steel, resulting in a limited understanding of whether the incorporation of the Fe3C microstructure enhances or alters the adsorption and dissociation behaviors of hydrogen on the surface of steel. MethodsUsing the first-principles method and density functional theory, unit cell models were established for two typical microstructures of high-grade steel: Fe3C and α-Fe. These models were employed to investigate hydrogen adsorption behaviors across different close-packed planes, adsorption sites, and adsorption angles. By taking the optimal adsorption configurations of the Fe3C and α-Fe phases as initial states, and based on the adsorption products simulated by the unit cell models, a search for transition states was conducted to describe the hydrogen dissociation process on the surface of high-grade steel. Subsequently, the adsorption energy required for H2 adsorption and dissociation, along with the corresponding dissociation energy barrier, were compared between the two unit cell models. Taking into account surface properties related to electronic charge density and density of states, additional analysis was conducted to explore the bonding mechanisms between hydrogen atoms and Fe and C atoms under the optimal adsorption configurations of the microstructure surfaces. ResultsThis study revealed the direct influence of close-packed planes, adsorption sites, and adsorption angles on the magnitude of adsorption energy. The optimal absorption configuration of the Fe3C phase was identified as the parallel adsorption of H2 at the Bgg site on the (100) plane, with an adsorption energy of −1.26 eV. In contrast, the optimal absorption configuration of the α-Fe phase was determined to be the parallel adsorption of H2 at the Tf site on the (110) plane, exhibiting an adsorption energy of −1.44 eV. The transformation of H2 molecules was observed to change from a perpendicular configuration to a parallel configuration prior to dissociation. The dissociation energy barrier for the Fe3C phase in its optimal absorption configuration was measured at 0.83 eV (79.97 kJ/mol), while that for the α-Fe phase was recorded at 0.46 eV (44.32 kJ/mol). During the dissociation and adsorption processes, the bonding force between Fe atoms was found to weaken due to the presence of H atoms. Additionally, the 1s orbital electrons of H atoms were found to be conjugated and hybridized with the 2s and 2p orbital electrons of surface C atoms, as well as with the 4s and 3d orbital electrons of surface Fe atoms. ConclusionThe study findings suggest correlations between the adsorption and dissociation capabilities of H2 on the surface of high-grade steel and the microstructure and surface structure of the steel. The Fe3C microstructure enhances the adsorption and dissociation behaviors of hydrogen on the steel surface, with the lowest dissociation energy occurring when H2 molecules are adsorbed parallel to the surface. In high-grade steel, H2 molecules are initially adsorbed on the α-Fe phase and partially on the Fe3C phase. The active H atoms generated by dissociation through orbital hybridization penetrate the steel, creating a necessary condition contributing to hydrogen damage.